Development of glycidyl methacrylate grafted irradiated fibers and poly(acrylonitrile-co-acrylic acid) microparticles adsorbents for the removal of p-nitrophenol - Saber, Almohamedabas Shihab Ezzuldin M (2021)
p-Nitrophenol (PNP) is one of the most hazardous pollutants; this compound is extremely damaging to human well-being and additionally, leads to both environmental and economic burdens. Several strategies have been utilized for the removal of phenols from effluents. The adsorption separation technique is considered to be an effective method; it is broadly utilized for wastewater treatment. Various adsorbent materials are used for the purification of phenols-contaminated effluent. However, they are subject to limitations due to their expense, high-energy requirement, relatively low adsorption capacities, slow kinetics and challenges related to their regeneration and recyclability. To overcome these challenges, novel fibrous and microparticle based adsorbents have been designed and employed for PNP adsorption from aqueous solution. Fibrous-based adsorbents were prepared by radiation-induced graft polymerization (RIG); glycidyl methacrylate (GMA) was grafted onto polyamide 6 (PA6) and natural cotton (Cot) substrates in order to form (PA6-g-GMA) and (Cot-g-GMA) fibers, respectively. The extent to which GMA was grafted on PA6 and cotton fibers was found to be markedly influenced by the absorbed dose of radiation and the reaction time of grafting. The optimal parameters were established so as to attain the required degree of grafting (DG) which tuned to 200% at 25 kGy absorbed dose and 30 minutes for PA6 whilst 10 kGy and 50 minutes for cotton fibers. A functionalization strategy was run with trimethylamine (TMA) to obtain TMA-(PA6-g-GMA) and TMA-(Cot-g-GMA). Redox polymerization (RP) of acrylonitrile (AN)/acrylic acid (AA) as poly(AN-co-AA) was employed so as to create microparticle-based adsorbents. A range of AA ratios were integrated into the polyacrylonitrile chain and additionally functionalized with an amidoxime (AO) moiety in order to generate AO-poly(AN-co-AA) adsorbents. The created adsorbents were evaluated so as to verify the copolymerization and functionalization processes and to describe the impact of preparation on the adsorbent's physiochemical properties utilizing a range of analytical strategies, including Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) analysis, Field emission scanning electron microscopy (FESEM), Brunauer–Emmett–Teller (BET) surface area, pore size assessment, Thermogravimetric (TG-DTG) analyzer and point of zero charge (pHpzc). Adsorption studies for PNP removal were conducted. The factors encompassing adsorbent dose, solution pH, temperature, initial PNP concentration and contact time were demonstrated to impact adsorption performance; this was optimized in depth. The adsorption process showed that the proportion of PNP removal increased when the adsorbent dose and PNP initial concentration were increased. The process of PNP adsorption was negatively affected by temperature, where a lower temperature was clearly preferable for greatest PNP adsorption. The adsorption was found to be pH-dependent; an increase in pH from 3.0 to 5.0 caused an increased in PNP removal, i.e. from 46.79% to 82.81% for TMA-(PA6-g-GMA) and from 49.31% to 85.33% for TMA-(Cot-g-GMA) whilst from 34.8% to 80.6% by changing the pH from 3 to 7. A pH of 5.0 was associated with maximum removal of PNP onto fibrous adsorbents and pH of 7 onto AO-poly(AN-co-AA) adsorbent. The function of the adsorbents pertaining to kinetics, equilibrium, isotherm, and thermodynamics of PNP adsorption from aqueous solutions was assessed employing relevant models. Non-linear Pseudo-first order (PFO), Pseudo-second order (PSO), Elovich and Intraparticle diffusion (IPD) models were utilized to study the adsorption kinetics; PNP adsorption on all adsorbents was demonstrated to follow to Pseudo-second order model. While non-linear Langmuir, Freundlich, Temkin and Redlich-Peterson models offered data on the adsorption isotherms; in which, Redlich Peterson most closely described the equilibrium results, followed closely by Langmuir isotherm and Freundlich isotherm models for the fibrous and microparticle-based adsorbents, respectively. The maximum adsorption capacities were TMA-(PA6-g-GMA), 176.04 mg/g; TMA-(Cot-g-GMA) 180.00 mg/g; and AO-poly(AN-co-AA), 143.06 mg/g. Thermodynamic evaluation demonstrated that the adsorption was a spontaneous and exothermic process. Lastly, the specific high regeneration efficiency of the adsorbents was revealed. The data from this study imply that fibrous adsorbents exhibit a higher adsorption capacity and more rapid kinetics than microparticle-based adsorbents. However, the latter have markedly higher adsorption capacity than alternative adsorbents described in previous studies. Therefore, it can be believed that the designed adsorbents are encouraging materials for the removal of PNP from water and wastewater.